EDUCATIONAL STANDARDS OF THE LEADING RUSSIAN UNIVERSITIES - Alexander I. Chuchalin (Высшее образование в России)
The paper considers the evolution of the state educational standards of higher education and the experience of leading Russian universities in the development and implementation of self-established educational standards. The peculiarities of creating their own educational standards in the various HEIs and the main differences from the federal state educational standards are identified. The trends in the development of educational standards at leading universities are determined. Attention is paid to the standards of master degree programmes in engineering and technology.